Diverse Morphology and Structural Features of Old and New World Hantaviruses - Amar Parvate; Evan P. Williams; Mariah K. Taylor; Yong-Kyu Chu; Jason Lanman; Erica Ollmann Saphire; Colleen B. Jonsson (Viruses, 2019)
To further understanding of the structure and morphology of the Orthohantavirus, family Hantaviridae, we have employed cryo-electron microscopy (cryo-EM) for three New World hantaviruses: Andes (ANDV), Sin Nombre (SNV), and Black Creek Canal (BCCV). Building upon our prior cryo-EM and cryo-tomography study of the Old World hantavirus, Hantaan virus (HTNV), we have expanded our studies to examine the entire virion population present in cell culture supernatant. Hence, in contrast to the prior cryo-EM/ET studies in which we used a polyethylene precipitation, a sucrose gradient, and a sucrose cushion, we used two sucrose cushions. We inactivated the material after the first cushion. We tested the method using HTNV which has a known cryo-EM structure and observed equivalent results. Therefore, we used this method to assess the particle distribution of the New World hantaviruses by cryo-EM. Cryo-EM images showed a diverse range of sizes and morphologies for the New World viruses that we classified as round, tubular, and irregular. Strikingly, BCCV virions were mostly tubular. These first cryo-EM images of the New World Orthohantavirus confirm prior EM observations that noted tubular projections of SNV at the plasma membrane during virion morphogenesis but were not confirmed. These findings underscore the need for further investigation of virion morphogenesis of the Orthohantavirus.